Analisis Kualitas Pelayanan Terhadap Kepuasan Publik Pada Kelurahan Lubuk Lintang Kecamatan Seluma - Nina Nina; Nia Indriasari; M. Rahman Febliansa (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
The purpose of this study was to determine the quality of public services, to determine the satisfaction of the public (community), and to determine the effect of service quality on public satisfaction in Lubuk Lintang Village, Seluma District. The main data of the research is data that comes from respondents through the distribution of questionnaires. Data analysis was carried out descriptively and quantitatively. Quantitative analysis used linear regression and t-test (t-test). The results showed that the quality of service provided by the Lubuk Lintang Village apparatus was quite good, the public (community) satisfaction with the services provided by the Lubuk Lintang Village apparatus, Seluma Subdistrict, was classified as good. The results of this study increase the quality of service can increase community satisfaction based on a linear regression coefficient of 0.300. The hypothesis that was previously proposed was proven, because the t count was the significance was 0.018 < 0.05 ..